Casper [videorecording (Blu-Ray)] - Ricci, Christina; Pullman, Bill; Moriarty, Cathy; Idle, Eric; Stoner, Sherri; Oliver, Deanna (Universal Pictures Home Entertainment, 2021)
Determined to get her hands on her father's hidden fortune, Carrigan is forced to hire an afterlife therapist to exercise the ghosts that keep frightening her away. Dr. Harvey and his daughter, Kat, move in and soon Kat meets Casper, the friendliest ghost. But Casper's uncles are still determined to drive all the "fleshies" away.